Home-country egalitarianism and cross-border nonmarket strategy - Kim, Jin Hyung; Siegel, Jordan I. (Journal of International Business Studies, 2026)
Cross-border nonmarket strategy—multinational enterprises’ choice of nonmarket strategic actions in pursuit of profitability in a host market—is an essential part of international business. Recent calls for research assert, however, that very little is known about how multinational enterprises choose among cross-border nonmarket strategies. We thus propose that egalitarianism—one type of home-country informal institution—is a key predictor of an important set of cross-border nonmarket strategy choices, particularly among corporate political activities with varying degrees of transparency. We further test this argument by incorporating a firm-level corporate governance measure related to transparency to see how the firm-level corporate governance moderates the main effect. Our study contributes to international business and nonmarket strategy research by highlighting the importance of home-country informal institutions as well as host-country formal institutions as a guiding principle in cross-border nonmarket strategy.